2002
DOI: 10.1103/physrevb.66.014505
|View full text |Cite
|
Sign up to set email alerts
|

Magnetization and microwave study of superconductingMgB2

Abstract: We report magnetic field dependent magnetization and microwave impedance measurements on a MgB 2 superconductor prepared by high pressure synthesis. We find that the upper critical field is linearly dependent on temperature near T c and the dc irreversibility field exponent is ~1.4. The microwave data display an excess surface resistance below T c which is neither observed in low T c nor in high temperature superconductors (HTSC). The real part of the complex conductivity, σ 1 , shows a huge maximum below T c … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 53 publications
1
6
0
Order By: Relevance
“…(1.22). This is an indication, in agreement with previous findings [143], of the collective nature of the pinning forces in this material. This conclusion is also supported by the low temperatures collapsing of all curves ν 0 (b), with b = B/B c2 (T ).…”
Section: Mgbsupporting
confidence: 93%
See 1 more Smart Citation
“…(1.22). This is an indication, in agreement with previous findings [143], of the collective nature of the pinning forces in this material. This conclusion is also supported by the low temperatures collapsing of all curves ν 0 (b), with b = B/B c2 (T ).…”
Section: Mgbsupporting
confidence: 93%
“…We remark that this is a nontrivial result: previous analysis have never been able to describe the microwave data using the same parameters obtained from low frequency measurements. In particular, the upper critical field was found to be field dependent [143] or anomalous field dependencies for the vortex viscosity were invoked [76].…”
Section: Mgbmentioning
confidence: 99%
“…δ v (ω, B, T ) depends on the relative magnitude of the viscous and restoring-pinning forces through the depinning frequency [29]. Since we are analyzing the results in a restrict range of temperature near T c , and considering the values of the depinning frequency reported in the literature for MgB 2 [10,30], it is reasonable to assume that the vortex motion at our working frequency is ruled by the viscous drag force, i.e. vortices move in the flux-flow regime.…”
Section: The Modelmentioning
confidence: 99%
“…Studies reported in the literature on the field-induced variations of R s in MgB 2 have highlighted several anomalies, especially at applied magnetic fields much lower than the upper critical field, among which unusually enhanced field-induced mw losses [8,9,10,11] and a magnetic hysteresis of unconventional shape [11,12,13]. It has been suggested that these anomalies are strictly related to the peculiarities of the fluxon lattice in MgB 2 .…”
Section: Introductionmentioning
confidence: 99%
“…where the exponent n is an indication of the different vortex dynamics. An exponent of n ∼ 1.5 was found for MgB 2 [171] which is due to a collective pinning commonly observed in LTSC. An exponent of n = 1.5 − 2 was found in HTSC Bi To investigate the doping dependent behavior of B irr , one can scale the irreversible field against B c2 (0) as shown in figure 4.20 by the zero temperature…”
Section: Irreversible Field B Irrmentioning
confidence: 79%